Oscillation sources and wave propagation paths in complex networks consisting of excitable nodes - 廖旭红 钱郁 弭元元 夏勤智 黄晓清 胡岗 (Frontiers of physics, 2011)
Self-sustained oscillations in complex networks consisting of nonoscillatory nodes have attracted long-standing interest in diverse natural and social systems. We study the self-sustained periodic oscillations in random networks consisting of excitable nodes. We reveal the underlying dynamic structure by applying a dominant phase-advanced driving method. The oscillation sources and wave propagation paths can be illustrated clearly via the dynamic structure revealed. Then we are able to control the oscillations with surprisingly high efficiency based on our understanding.